Avaliação endócrino-metabólica de pacientes com anemia falciforme: uma coorte de dez anos - Gomes, Ingrid Cristiane Pereira (2016)
Sickle cell anaemia (SCA), the most prevalent hereditary disease in the world, presents, among many complications, endocrine-metabolic changes, especially growth retardation and puberty in children and adolescents. The final height of adults with SCA is, however, still controversial and there are few studies about it in literature. This dissertation consists of two original articles. In the first article, "Growth and puberty in a prospective cohort of patients with sickle cell anemia: assessment in ten years", it was observed that patients with SCA showed growth impairment and pubertal delay when compared to healthy controls, however, albeit belatedly, they reach normal sexual maturation. Moreover, they reached normal height in adulthood, unlike what occurred with weight and BMI, finding even more evident in males. In the second article, "Endocrine-metabolic profile of adults with sickle cell anemia", it was observed that men with SCA had higher levels of gonadotropins than controls. Levels of high density lipoprotein (HDL) and low density lipoprotein (LDL) cholesterol were lower in the SCA group. The high prevalence of low HDL (96%) in the SCA group and its positive correlation with the hemoglobin concentration and its negative correlation with reticulocytes count and leukocytes count the possibility of HDL be considered a marker to assist in predicting adverse clinical events in this population. Although it has not been observed difference in the levels of 25-hydroxyvitamin between the groups, there was a higher prevalence of its deficiency and insufficiency in SCA group, which enhances the risk, already existing in this population, of osteoporosis. The findings of both studies characterize patients with SCA about the evolution of their growth and development into adulthood and show endocrinemetabolic changes that deserve to be investigated during follow-up, in order to prevent other complications that can compromise their quality life.